Strategi Pengembangan Kompetensi Sosial-Emosional Bagi Guru Paud - Paur Gun, Florensius (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to analyze the strategies for developing social-emotional competencies among Early Childhood Education (ECE) teachers and their impact on teaching quality and classroom management. A qualitative approach with a case study design was employed, involving in-depth interviews, participatory observations, and document analysis. The findings show that social-emotional training attended by ECE teachers significantly enhanced their ability to manage emotions, communicate effectively, and create a classroom climate that supports children's social-emotional development. However, challenges such as limited time and crowded classrooms posed barriers to the consistent application of the skills learned. This study suggests the need for ongoing evaluation and a strong school culture to optimize the development of teachers' social-emotional competencies. In conclusion, the development of social-emotional competencies for ECE teachers has been shown to improve teaching quality, teacher-child relationships, and create a more inclusive learning environment that supports overall child development.